The Influence of Transformasional Leadership Style and Organizational Culture on Employee Performance with Motivation as an Intervening Variabel: Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening - Maulana, Mochamad Luthfi; Oetarjo, Mas (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of transformational leadership style and organizational culture on employee performance with motivation as an intervening variable in UKM Sumber Lancar Keramik. This research uses quantitative research with hypothesis testing. The sample used in this study were 50 employees at UKM Sumber Lancar Keramic. The analytical tool used in this research is path analysis technique with the help of SmartPLS (Partial Least Square) software version 3.0 for windows. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of this study prove that (1) transformational leadership style is positively and significantly related to motivation, (2) organizational culture is positively and significantly related to motivation, (3) transformational leadership style has positive and insignificant effect on employee performance, (4) organizational culture positive and insignificant effect on employee performance, (5) motivation is positively and significantly related to employee performance, (6) leadership style is positively and significantly related to employee performance with motivation as an intervening variable, (7) organizational culture is positively and significantly related to performance employees with motivation as an intervening variable.